The Optimal Profit Repairing Policy of One-component Multistate System with Graduate Failure - Ilijoski, Bojan; Mihova, Marija (My University, 2012)
We regard a multi-state one component system with graduate failure. The one level transitions are homogeneous Markov transitions and the unit time work in the state i makes profit Ci . We suppose that the system runs during n periods with constant length T and after each period we are able to make an inspection of the system. Depending of its current state we can decide to repair it or not. The problem is to find the optimum policy for repairing such that the summary profit be the greatest one.